Effect of environmental variables on buffaloes physiology - Botigeli Sevegnani, K. [UNESP]; Macedo de Toledo, L.; Arcaro Junior, I.; Schneider, P. [UNESP]; Matarazzo, S. V.; Tonizza de Carvalho, N. A.; Ambrosio, L. A. (Pagepress Publ, 2007)
The objective of this work was to evaluate the effect of environmental variables on dairy buffaloes physiology in two different places after milking, shaded plus artificial ventilation and another one non-shaded, in Ribeira Valley, São Paulo State, Brazil. Data on the respiratory rate (RR) and the surface temperature (ST) at udder, neckmiddle, forehead, back middle and rump were collected in 12 dairy buffaloes at autumn. In the same way, it were recorded the black globe temperature in the sun (GTS) and in the shade (GTNS), air temperature and wind speed at padronized height of 1.60 meters. All data were collected at 10:30am and 1:30pm. The results showed statistical difference among black globe temperature, wind speed, RR and ST (P<0.01) in two treatments.The results showed the necessity of protection against the solar radiation in the buffaloes, even in periods of warm climates.
Keywords: Respiratory rate; Thermal comfort; Buffaloes production